Language Evolution in the Age of the Internet and Social Media (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Internet and social media have profoundly transformed modern language and communication, serving as catalysts for linguistic innovation and change. This study examines the ways in which digital platforms influence language evolution, focusing on the emergence of new expressions, shifts in grammar and syntax, and the rise of visual communication through emojis and memes. Online interactions promote brevity and adaptability, leading to the widespread use of abbreviations, acronyms, and informal speech patterns. Additionally, the global nature of the Internet facilitates the exchange of linguistic elements across cultures, while providing to platforms for endangered languages to thrive. This dual role—promoting both linguistic homogenization and diversification—raises questions about the long-term effects of digital communication on linguistic identity and cultural heritage. The article concludes by considering the implications of these changes for education, sociolinguistics, and language preservation in the digital age.